1995
DOI: 10.1577/1548-8659(1995)124<0845:dappow>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Potential Production of White Sturgeon in the Unimpounded Lower Columbia River

Abstract: The unimpounded lower Columbia River downstream from Bonneville Dam (LCR) supports the greatest abundance and density of white sturgeon Acipenser transmontanus reported in the species' range. The high productivity of the population resulted from growth that was as good as or better than reported for other populations, the highest mean relative weight reported for any white sturgeon population, and a relatively low median age (24 years) of first maturity for females (95% of females matured between 16 and 35 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 12 publications
3
52
1
Order By: Relevance
“…Welch and Beamesderfer (1995) found 37% of the females > 166 cm FL in Bonneville, The Dalles, and John Day Reservoirs were maturing (equivalent to Stages 3 and 4 in this study), while 10% of the females were mature or spent (equivalent to Stages 5 and 7 in this study), similar to this study. DeVore et al (1995) found 2% of the females > 110 cm FL below Bonneville Dam were ripe or spent (equivalent to Stages 5 and 7 in this study), which is lower than the percent in this study and may be an effect of inclusion of fish > 110 cm FL. While 10% of the adult females in this study were capable of or had spawned successfully, 25% of the adult males were capable of or had spawned successfully, which is identical to the values reported in 2006.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Welch and Beamesderfer (1995) found 37% of the females > 166 cm FL in Bonneville, The Dalles, and John Day Reservoirs were maturing (equivalent to Stages 3 and 4 in this study), while 10% of the females were mature or spent (equivalent to Stages 5 and 7 in this study), similar to this study. DeVore et al (1995) found 2% of the females > 110 cm FL below Bonneville Dam were ripe or spent (equivalent to Stages 5 and 7 in this study), which is lower than the percent in this study and may be an effect of inclusion of fish > 110 cm FL. While 10% of the adult females in this study were capable of or had spawned successfully, 25% of the adult males were capable of or had spawned successfully, which is identical to the values reported in 2006.…”
Section: Discussioncontrasting
confidence: 80%
“…Exact knowledge of the maturation cycle in white sturgeon in the Columbia River requires following the stage of development in individual fish over many years. Females in all stages of development were found throughout the winter and spring below Bonneville Dam which is consistent with a maturation cycle longer than one year, as previously discussed for white sturgeon by DeVore et al (1995) and Doroshov et al (1997). The data collected from recaptured adult fish below Bonneville Dam in [2000][2001][2002][2003][2004][2005][2006][2007] revealed that males of reproductive size are not spawning every year unlike in culture.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, many populations have become decimated despite their historical abundance and widespread distribution across the Northern Hemisphere (Birstein 1993, Bemis & Findeis 1994, DeVore et al 1995. Nonregulated harvests for the highly sought caviar and meat of many sturgeon species initiated their decline in the mid-1800s in North America (Birstein 1993, Bemis & Findeis 1994, Pikitch et al 2005, exacerbated stock declines from the Caspian Sea in the early 1960s (Khodorevskaya et al 1997, Ivanov et al 1999, Khodorevskaya & Krasikov 1999) and continue to depress or limit the recovery of some populations (Khodorevskaya et al 1997, Williamson 2003, Peterson et al 2007, Johnson & Iyengar 2015.…”
Section: Global Decline Of Acipenseriformesmentioning
confidence: 99%
“…Its highest population densities occur in the estuaries of large rivers (Monaco and Nelson 1990:86;DeVore et al 1995:845). The Columbia River is regarded as the most productive white sturgeon habitat in North America (Collette 1989;Devore et al 1995).…”
Section: Anadromous Fish White Sturgeon Acipenser Transmontanusmentioning
confidence: 99%